PASANG SURUT PERAN MASYARAKAT BUGIS PADA MASA KESULTANAN KUTAI KARTANEGARA: DALAM NASKAH KUNA DARI KOTABANGUN - Mujib Mujib (Balai Arkeologi Kalimantan Selatan, 2009)
An old Latin manuscript in Malay language, in the possession Awang Sabirin, was documented during the archaeological research in Kotabangun in 2007. The manuscript was a copy a typed-text from an older manuscript written during the Dutch occupation. It is assumed that the text is another version of Salasilah Kutai Kartanegara written in the 17th century. This manuscript describes related events between the Kutai Kartanegara Kingdom and the role of the Buginese within the kingdom’s sovereignty. I assume the Buginese had played an important role then and it is essential to carry out an intensive multidisciplinary study on such subject based on archaeology, philology, history, and sociology. This article discusses the content of the manuscript and the role Buginese in Kutai Karatnegara.